A tree partitioning dynamic policy for OVSF codes assignment in wideband CDMA. - Dell'Amico, M. (IEEE Transactions on wireless communications)
This paper proposes some novel techniques to accommodate users with different rate requirements in a wideband code-division multiple-access system employing orthogonal variable spreading factor codes. Two simple static code assignment strategies are first considered, and an improvement based on multicode assignment. Then the new idea of tree partitioning is introduced and used to devise a dynamic code reassignment algorithm. The behavior of these different techniques is experimentally investigated, in terms of call blocking probability and number of required reassignments. The tree partitioning method exhibits very good performances.